Dimethyl Sulfide‐Induced Increase in Cloud Condensation Nuclei in the Arctic Atmosphere. Issue 7 (9th July 2021) - Park, Ki‐Tae; Yoon, Young Jun; Lee, Kitack; Tunved, Peter; Krejci, Radovan; Ström, Johan; Jang, Eunho; Kang, Hyo Jin; Jang, Sehyun; Park, Jiyeon; Lee, Bang Yong; Traversi, Rita; et al.
Abstract: Oceanic dimethyl sulfide (DMS) emissions have been recognized as a biological regulator of climate by contributing to cloud formation. Despite decades of research, the climatic role of DMS remains ambiguous largely because of limited observational evidence for DMS‐induced cloud condensation nuclei (CCN) enhancement. Here, we report concurrent measurement of DMS, physiochemical properties of aerosol particles, and CCN in the Arctic atmosphere during the phytoplankton bloom period of 2010. We encountered multiple episodes of new particle formation (NPF) and particle growth when DMS mixing ratios were both low and high. The growth of particles to sizes at which they can act as CCN accelerated in response to an increase in atmospheric DMS. Explicitly, the sequential increase in all relevant parameters (including the source rate of condensable vapor, the growth rate of particles, Aitken mode particles, hygroscopicity, and CCN) was pronounced at the DMS‐derived NPF and particle growth events. This field study unequivocally demonstrates the previously unconfirmed roles of DMS in the growth of particles into climate‐relevant size and eventual CCN activation. Plain Language Summary: Marine phytoplankton can produce gaseous dimethyl sulfide (DMS), which is the most abundant form of sulfur released into the atmosphere through sea‐air gas exchange. The polar oceans are known to be the most productive ocean in terms of DMS due to the high abundance of DMS‐producing phytoplankton. The oceanic emission of DMS into the marine atmosphere has received substantial attention during the last 30 years because of its contribution to cloud formation and its subsequent impact on climate. However, the climate feedback role of DMS remains uncertain due to insufficient evidence supporting DMS‐derived formation of aerosol particles and their subsequent activation into cloud condensation nuclei (CCN), in turn affecting the Earth's radiation budget. In this study, we analyzed atmospheric DMS mixing ratios, and concentrations of aerosol particles and CCN in the Arctic atmosphere during the phytoplankton bloom period. Our results show that atmospheric DMS affects the formation and growth of aerosol particles and significantly contributes to CCN populations. Key Points: Dimethyl sulfide (DMS), aerosol particle numbers, and cloud condensation nuclei (CCN) were measured in the Arctic atmosphere Multiple episodes of new particle formation and particle growth with both high and low DMS mixing ratios were observed An increase in CCN was observed when the formation and growth of aerosol particles derived from DMS occurred